STUDY OF THE TOURIST AND RECREATIONAL LOAD IN THE “KOLSAI LAKES” STATE NATIONAL NATURE PARK, KAZAKHSTAN - Alexander ARTEMYEV; Sholpan ABDREYEVA; Ruslan BAIBURIEV; Azamat BEISAKHMET; Aida KALIYEVA; Aigul ABZHAPPAROVA; Armanay SAVANCHIYEVA; Lóránt Dénes DÁVID (Geo Journal of Tourism and Geosites)
The growing popularity of ecological tourism has led to a significant increase in tourist flows and, consequently, a rise in anthropogenic impacts on the ecosystems of natural areas. This phenomenon poses challenges to the delicate balance of these ecosystems, requiring detailed study and intervention. Studying the dynamics of this process is essential to assess its impact and develop effective measures to prevent critical stress that could lead to irreversible negative changes in the natu ral environment. The transition to circular tourism is also a major challenge. Using the example of the State National Natural Park “Kolsai Lakes,” located in the southeast of the Almaty region of Kazakhstan, the authors proposed a comprehensive approach to determining the maximum permissible tourist and recreational load. This approach includes expert assessments, calculation methods, and systematic monitoring observations to evaluate the capacity of the park's ecological routes and paths. The research focused on ensuring that these natural areas can sustain their ecological integrity while accommodating visitors. The practical outcomes of the research included the development of recommendations aimed at reducing anthropogenic impacts on the park's routes and paths. These recommendations encompass a combination of te chnical solutions, organizational strategies, and managerial measures designed to balance tourism with environmental preservation. The measures proposed align with global principles of sustainable tourism and reflect the need for integrated approaches to managing natural resources. The main results emphasize the critical importance of sustainable management methods in maintaining the ecological integrity of the “Kolsai Lakes” State National Nature Park. These findings were derived from field research, where the authors conducted on-site evaluations to gather data and analyze the environmental conditions. The insights gained were systematically organized and presented in tabular form within the article. The study underlines the necessity of ongoing monitoring and adaptive management to address the evolving challenges posed by ecological tourism. By implementing the recommended measures, the park authorities can mitigate potential environmental risks while fostering a harmonious relationship between tourism and nature conservation. This research contributes valuable knowledge to the field of sustainable tourism, offering practical strategies that can be applied to other natural areas facing similar challenges.